Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Pada Angkringan Batang Batu Di Tenggarong - Amiruddin, Amiruddin; Suprapto, Heru; Erwinsyah, Erwinsyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract :In this research research obyek to check Angkringan Batang Batu representing a effort providing food and beverage with open natural atmosphere berlamat walked A.M. Sangaji No.27 Rt.9 Sub District Of Sukarame District of Tenggarong with owner Mr. Aria of Nurzaman. As for sold food and beverage Angkringan Batang Batu like fried rice, noodles fry, cheese banana and still many again and also assorted beverage and juice of sop fruit which enthused many consumer to relax nighttime. Intention of this research is to know how big influence of Atmosphere variable of Angkringan, Quality of Product and Image (Image) influencing Satisfaction Of Consumer Angkringan Batang Batu Tenggarong and know most dominant influence of independent variable which influence Satisfaction Of Consumer Angkringan Batang Batu Tenggarong. In data analysis, as according to research object where variable suspected more than one, hence analysis utilized for the verification of hypothesis in this research quantitative analysis with model of Multiple Regresi. Based on the description, it can be concluded that the first hypothesis stated stated